Addressing Temporal Change in Strategic Groups Analysis: A Three-Mode Factor Analysis Approach - BAIRD, Inga S. (Institutional Knowledge at Singapore Management University, 1988)
This paper focuses upon the issue of considering temporal changes in strategy as well as temporal variations in the importance of strategic criterion variables when analyzing the strategic group structure within industries. Three-mode factor analysis is proposed as a procedure to allow such joint considerations. The usefulness of this procedure is further demonstrated through an example set in the computer industry.